Acid base homeostasis and serum bicarbonate concentration in syndrome of inappropriate anti-diuretic hormone secretion (SIADH) with hyponatremia - Soleimani, Manoocher (Frontiers in Endocrinology, 2023)
The Syndrome of Inappropriate ADH secretion (SIADH) presents with excess ADH release caused by a range of conditions; including pneumonia, brain tumors, certain lung cancers, and diseases of the hypothalamus. It presents with significant reduction in both sodium and chloride concentrations in the blood. However, reports examining the acid base status indicate a normal serum bicarbonate concentration and systemic acid base homeostasis. The mechanisms for the absence of abnormalities in acid base homeostasis remain speculative. This mini review is highlighting the recent advances in renal molecular physiology to provide answers for the maintenance of acid base status and serum bicarbonate in a physiological range.